Atlas of Peripheral Nerve Ultrasound With Anatomic and MRI Correlation - Peer, Siegfried; Gruber, Hannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
In recent years, sonography of the peripheral nervous system has gained widespread acceptance. New diagnostic applications have emerged, and the field of ultrasound-guided interventions has expanded significantly: regional anesthesia, peripheral nerve blocks, and similar techniques are now frequently performed under ultrasound guidance by anesthesiologists and pain physicians alike. This atlas of peripheral nerve ultrasound is designed to meet the daily needs of both radiologists and clinicians by allowing rapid review of typical features, knowledge of which is important for successful diagnosis and intervention. The side by side presentation of ultrasound images with anatomical cryosections and photographs of transducer positions allows for reliable sonographic identification of even tiny nerves in regions of complex topography. The practical value of the atlas is further enhanced by correlations with high-resolution MRI scans and the inclusion of advice on state of the art examination techniques.
Introduction to High Resolution Sonography of the Peripheral Nervous System: General Considerations and Examination Technique -- Introduction to Magnetic Resonance Imaging of the Peripheral Nervous System: General Considerations and Examination Technique -- Nerves in the Head and Neck -- Upper Extremity Nerves -- Lower Extremity Nerves -- Nerves in the Trunk and Abdominal Wall.
Keywords: Medicine; Radiology, Medical; Diagnosis, Ultrasonic; Medicine & Public Health; Imaging / Radiology; Neuroradiology; Ultrasound